BackTrack 5 R2 wireless penetration testing your hands-on guide to wireless penetration testing using Backtrack 5 / Farrukh Haroon. - Haroon, Farrukh; Safari eBooks ([S.l.] : Packt Pub., 2013)
"This course is aimed at security professionals and IT professionals who want to learn about wireless penetration testing using the BackTrack Linux security distribution. The course assumes that you already know the basics of wireless networks and can operate at least one Linux distribution. Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. Designed as a practical video tutorial with step-by-step instructions to teach you about Wireless Penetration Testing, the course has been designed to ensure that topics are presented in a gradual manner, allowing you to grasp the information that's being presented before moving on to more advanced topics"--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed Oct. 15, 2013).
Presenter, Farrukh Haroon.
Keywords: Penetration testing (Computer security); Computer software -- Testing; Electronic books